Study on static characteristics of a novel prestress-reinforced railway subgrade - Junli Dong; Fang Xu; Qishu Zhang; Wuming Leng; Yafeng Li; Qi Yang (Railway Engineering Science)
Abstract Understanding the reinforcement effect of the newly developed prestressed reinforcement components (PRCs) (a system composed of prestressed steel bars (PSBs), protective sleeves, lateral pressure plates (LPPs), and anchoring elements) is technically significant for the rational design of prestressed subgrade. A three-dimensional finite element model was established and verified based on a novel static model test and utilized to systematically analyze the influence of prestress levels and reinforcement modes on the reinforcement effect of the subgrade. The results show that the PRCs provide additional confining pressure to the subgrade through the diffusion effect of the prestress, which can therefore effectively improve the service performance of the subgrade. Compared to the unreinforced conventional subgrades, the settlements of prestress-reinforced subgrades are reduced. The settlement attenuation rate (R s) near the LPPs is larger than that at the subgrade center, and increasing the prestress positively contributes to the stability of the subgrade structure. In the multi-row reinforcement mode, the reinforcement effect of PRCs can extend from the reinforced area to the unreinforced area. In addition, as the horizontal distance from the LPPs increases, the additional confining pressure converted by the PSBs and LPPs gradually diminishes when spreading to the core load bearing area of the subgrade, resulting in a decrease in the R s. Under the single-row reinforcement mode, PRCs can be strategically arranged according to the local areas where subgrade defects readily occurred or observed, to obtain the desired reinforcement effect. Moreover, excessive prestress should not be applied near the subgrade shoulder line to avoid the shear failure of the subgrade shoulder. PRCs can be flexibly used for preventing and treating various subgrade defects of newly constructed or existing railway lines, achieving targeted and classified prevention, and effectively improving the bearing performance and deformation resistance of the subgrade. The research results are instructive for further elucidating the prestress reinforcement effect of PRCs on railway subgrades.